Image, text, corpus in the stories of Narcisus and Pygmalion in Ovid's "Metamorphoses" - Darab, Ágnes (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The article offers a comparative analysis of Ovid’s stories of Narcissus and Pygmalion. The analysis highlights the intertextual link between the two narratives, and uses it as the basis for comparison, focusing on the single aspect: who creates what, and how. The paper concludes that what is at stake in the two texts at a fundamental level can be found in the sphere of aesthetics